Inženirske računalniške simulacije v konstrukterstvu: univerzitetni učbenik - Ren, Zoran; Ulbin, Miran; Vesenjak, Matej (University of Maribor Press, 2018)
Engineering Computational Simulations in Mechanical Design: University Textbook. The textbook covers the field of engineering computational simulations and is intended as a study aid for the lectures on Engineering computational simulations and Computational simulations in mechanical design, and indirectly in Engineering Tools 2 and Computational solid mechanics. It contains the explanation of the entire contents that the students must acquire in these subjects and is in accordance with the curriculum of the mentioned subjects.